Exploration of the Use of Artificial Intelligence in Business Processing by KOL Marketing Agencies - Satria, Ryuki (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study aims to examine the use of Lark's Artificial Intelligence (AI) platform in supporting business processes in Key Opinion Leader (KOL) marketing agencies, with a case study on Orbeat Digital Agency. The research method used is a qualitative approach with data collection techniques in the form of participatory observation, semi-structured interviews, and documentation. The results show that Lark plays a significant role in improving operational efficiency, strengthening team coordination, and facilitating real-time management of campaign projects. However, there are still obstacles such as the need for a stable internet connection and the process of adapting new users. This study recommends strengthening digital infrastructure and internal training to optimize the use of Lark.